2019
DOI: 10.5812/jjm.88521
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis of Key Players Associated with Fluconazole Resistance in Candida albicans

Abstract: Background: Fluconazole resistance in Candida albicans has become a serious public health problem. Most previous studies have focused on deciphering the relationship between fluconazole resistance and amino acid substitutions in ERG11, which encodes cytochrome P450 lanosterol 14α-demethylase whose enzymatic activity is inhibited by azoles. However, azole resistance in C. albicans is a multifactorial phenomenon and several lines of evidence indicate that other genes and mechanisms may contribute to the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Furthermore, Fathi et al found ERG11 gene expression in the azole-resistant isolates group was more than its expression in the azolesusceptible group [32]. On the contrary, Zhang et al did not find any difference in the expression of ERG11 genes between the fluconazole-susceptible and resistant isolates [33].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Fathi et al found ERG11 gene expression in the azole-resistant isolates group was more than its expression in the azolesusceptible group [32]. On the contrary, Zhang et al did not find any difference in the expression of ERG11 genes between the fluconazole-susceptible and resistant isolates [33].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Zhang et al 23 and Salari et al 32 reported that there was no difference in the expression of ERG11 genes among the fluconazole-susceptible and resistant strains.…”
Section: Various Species Of Candida Ie C Albicans and Non-albicansmentioning
confidence: 94%